Cannabis use disorder and dissociation: A report from a prospective first-episode psychosis study. (1st December 2021) - Ricci, V.; Ceci, F.; Di Carlo, F.; Lalli, A.; Ciavoni, L.; Mosca, A.; Sepede, G.; Salone, A.; Quattrone, D.; Fraticelli, S.; Maina, G.; Martinotti, G.
Abstract: Background: Cannabis is the most used recreational drug worldwide. Its use can increase the risk of developing psychotic disorders and exacerbate their course. However, the relationship between cannabis use and dissociative symptoms has been scarcely investigated. Aims: To examine differences in psychotic and dissociative symptoms, and in functioning in first-episode psychotic patients (FEPp) using cannabis compared with those not using cannabis. Methods: Between January 2014 and December 2019, seventy FEPp with cannabis use disorder (N = 35) and without it (N = 35) were recruited in psychiatric inpatient facilities in the Italian regions of Lazio and Piemonte. All subjects were assessed at FEP, after 4 and 8 months, using the Positive and Negative Syndrome Scale (PANSS), the Global Assessment of Functioning (GAF) scale and the Dissociative Experiences Scale – II (DES-II). Detailed information on the pattern of cannabis and other substance use were collected. Results: FEP using cannabis showed higher levels of positive symptomatology, dissociative experiences and worse functioning than their non-user counterpart, despite a comparable antipsychotic treatment. At an eight-month prospective evaluation, FEP using cannabis still showed higher levels of positive symptomatology and dissociation. Moreover, global functioning worsened over time in FEPp using cannabis, whereas it improved those not using it. Discussion: Our findings suggest that a greater degree of dissociation and positive symptoms at FEPp and their persistence over time may characterise cannabis-associated psychosis. Both these factors might explain the overall functioning worsening over time that we observed in the cannabis-user group compared to the functioning improvement in the non-user group. Highlights: Cannabis-associated psychosis show unique characteristics at onset and over time. Cannabis plays a role in inducing a greater state of dissociation. Cannabis users experience more positive symptoms and worse functioning. DES-II shows a higher score for high-potency cannabis compared to the lower one.